(untitled) (International Journal of Engineering and Computer Science, 2017)
The emerging studies and researches are based on the science platform of samples of DNA which need to perform various experiments for new findings in researches and their implementations. The analysis of DNA samples is carried out in various labs under controlled temperature environment. Barcoding lab and research facility provide barcoding training to researchers and facilities for them to work on their DNA samples and data generation. There is a necessity of maintaining the required temperature for specific amount of time which is favourable for experiment. A need of controlled environment for the various experiments is necessary for having the maximum accuracy in respective researches done with DNA samples. The controlled environment should have the desired specifications which are suitable for carrying out all multiple experiments on the samples which also should have an additional feature of continuously monitoring, controlling as well as agitating. There are many devices which perform same function but the major difference occurs is the cost. In this paper, we are proposing a dry block heating system which is a compact device which provides a wide range of temperature for the various applications carried out in DNA labs. The efficiency of such devices can be calculated according to the uniformity of temperature inside the chamber and the accuracy of the temperature sensor. A variable agitator provides continuous agitations to samples which avoids the formation of the precipitate during the heating of the samples. Micro-tubes are used which are crystal clear and hold the samples in it which are then processed in the device according to individual experiment. This device is mainly useful for the small scale industries which have low capital and can prove beneficial for new researchers.